Molecular Mechanisms and Epigenetic Regulation in Diabetic Cardiomyopathy - Mittal, Anupam; Garg, Rajni; Bahl, Ajay; Khullar, Madhu (Frontiers in Cardiovascular Medicine, 2021)
Diabetes mellitus (DM) is an important lifestyle disease. Type 2 diabetes is one of the prime contributors to cardiovascular diseases (CVD) and diabetic cardiomyopathy (DbCM), and leads to increased disease morbidity and mortality in DM patients. DbCM is a typical cardiac disease, characterized by cardiac remodelling in the presence of DM and in the absence of other comorbidities like hypertension, valvular diseases, and coronary artery disease. DbCM is associated with defective cardiac metabolism, altered mitochondrial structure and function, and other physiological and pathophysiological signalling mechanisms like oxidative stress, inflammation, myocardial apoptosis, and autophagy. Epigenetic modifiers are crucial players in the pathogenesis of DbCM. Thus, it is important to explore the role of epigenetic modifiers/modifications in regulating molecular pathways associated with DbCM. In this review, we have discussed the role of various epigenetic mechanisms like histone modifications (acetylation and methylation), DNA methylation, non-coding RNAs in modulating molecular pathways involved in the pathophysiology of the DbCM.